PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROTATING TRIO EXCHANGE DALAM MENINGKATKAN AKTIVITAS BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS V DI SDN 1 TANJUNG ALI - Irja Putra Pratama (STAI Pelabuhan Ratu, 2020)
This research was conducted to determine how the application of the rotating trio exchange (RTE) cooperative learning model in the fifth grade Islamic Religious Education subject at SDN 1 Tanjung Ali, in addition to finding out how the learning activities of students before and after the implementation of the RTE type cooperative learning model and also to find out how much influence the application of the type of RTE cooperative learning model in increasing the learning activities of students. The type of research used is experimental research with one group pretest-posttest design. The research approach is to use a quantitative approach. Furthermore, the data collection method used is the method of observation, questionnaires and documentation. The results obtained are the implementation of the RTE type cooperative learning model implemented in three stages, namely the planning stage, the implementation stage and the evaluation stage. The results of learning activities before implementing the RTE type of cooperative learning model were 6 students (15%) high, 26 students (65%) and 8 students (20%) low. The results of learning activities before implementing the RTE type of cooperative learning model were high learning activities: 9 students (22.5%), 25 students (62.5%) classified as low and 6 students (62.5%) classified as low (15%)). Based on the results of the pre-test and post-test above, the results of the calculation with the